Detection and characterization of bioaerosol emissions from wastewater treatment plants: Challenges and opportunities - Tian, Jianghan; Yan, Cheng; Garcia Alcega, Sonia; Hassard, Francis; Tyrrel, Sean; Coulon, Frederic; Nasir, Zaheer A. (Frontiers, 2022)
Rapid population growth and urbanization process have led to increasing demand for wastewater treatment capacity resulting in a non-negligible increase of wastewater treatment plants (WWTPs) in several cities around the world. Bioaerosol emissions from WWTPs may pose adverse health risks to the sewage workers and nearby residents, which raises increasing public health concerns. However, there are still significant knowledge gaps on the interplay between process-based bioaerosol characteristics and exposures and the quantification of health risk which limit our ability to design effective risk assessment and management strategies. This review provides a critical overview of the existing knowledge of bioaerosol emissions from WWTPs including their nature, magnitude and size distribution, and highlights the shortcoming associated with existing sampling and analysis methods. The recent advancements made for rapid detection of bioaerosols are then discussed, especially the emerging real time detection methods to highlight the directions for future research needs to advance the knowledge on bioaerosol emissions from WWTPs.
Keywords: bioaerosol; wastewater treatment plant; real time detection; emission characteristics; in situ measurement